Article RETRACTED due to malpractice Methodological Approach to Addressing Joint Replacement Challenges in Osteopetrosis: A Clinical Review Perspective - sen, Rimmi (Retos, 2026)
Osteopetrosis is considered a source of concern and a health problem because it is a rare disease that is difficult to detect and leads to many health risks. Osteopetrosis is a rare condition represented by a process disrupting normal bone formation and remodeling, which causes deformation of the teeth and skeleton, this deformity develops over time, causing an imbalance in the mineral balance. Also, osteopetrosis appears due to increased bone thickness and defective formation and disorganization, especially in areas of concentrated stress, such as the subtrochanteric areas, hip, knee, and femoral neck. The complication of osteopetrosis is degenerative osteoarthritis (OA) and directly affects hip or knee replacement operations in patients. The present review summarizes the most important previous and contemporary information and concepts and provides a detailed description of osteopetrosis, its causes, and risks that can be found in previous reviews and literature. In addition, the most important information and results reached in this literature regarding hip and knee joint replacement and its relationship to osteopetrosis.  In our review, we emphasize the need to evaluate the results of recent studies related to osteopetrosis and its relationship to hip and knee joint replacements and how to detect and deal with this disease. In addition, it contributes to providing evidence-based information to help clinicians and researchers evaluate osteopetrosis and its impact on the hip and knee joints and increase their motivation to pay attention to this field.